2011
DOI: 10.1007/s10535-011-0124-5
|View full text |Cite
|
Sign up to set email alerts
|

High frequency plant regeneration from the mature seeds of Garcinia indica

Abstract: A high frequency plant regeneration system was developed for the production of high yielding elite clones of Garcinia indica via direct organogenesis. A maximum number of 86.2 shoot buds per explant were induced from the mature seed segments cultured on Woody plant medium (WPM) supplemented with 2.0 mg dm -3 N 6 -benzyladenine and 1 mg dm -3 indole-3-acetic acid. Rooting was achieved on half-strength WPM medium supplemented with 3 mg dm -3 indole-3-butyric acid. Rooted plantlets were acclimatized and transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…80-100 % of explants developed 1-3 shoots on medium supplemented with KN, whereas TDZ-supplemented medium was not beneficial in shoot bud differentiation and explants remained green even after subculturing to fresh medium. The superiority of BAP on shoot bud induction was previously reported for G. mangostana (Goh et al 1990;Huang et al 2000) and G. indica (Malik et al 2005;Baskaran and Krishnan 2011). Similar effect of BAP in inducing multiple shoots has been reported for tree species such as F. limonia (Hiregoudar et al 2003), V. trifolia (Hiregoudar et al 2006) and Salix pseudolasigyne (Park et al 2008).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…80-100 % of explants developed 1-3 shoots on medium supplemented with KN, whereas TDZ-supplemented medium was not beneficial in shoot bud differentiation and explants remained green even after subculturing to fresh medium. The superiority of BAP on shoot bud induction was previously reported for G. mangostana (Goh et al 1990;Huang et al 2000) and G. indica (Malik et al 2005;Baskaran and Krishnan 2011). Similar effect of BAP in inducing multiple shoots has been reported for tree species such as F. limonia (Hiregoudar et al 2003), V. trifolia (Hiregoudar et al 2006) and Salix pseudolasigyne (Park et al 2008).…”
Section: Resultssupporting
confidence: 80%
“…1c). Malik et al (2005), Baskaran and Krishnan (2011) observed similar response of swelling of seed explants along with shoot bud differentiation on the medium supplemented with growth regulators in G. indica. Development of somatic embryos was reported by Thengane et al (2006) on immature seed explants of G. indica.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The propagation of this species through seeds is difficult, its seeds have a short shelf life and propagation through softwood grafting is not effective. There are many reports on the regeneration of different Garcinia species through in vitro micropropagation such as Garcinia xanthochymus [10], G. mangostana [11,12], and G. indica [13][14][15]. However, there are no regeneration protocols for the mass multiplication and conservation of Garcinia livingstonei, therefore the present investigation was taken up to develop an efficient in vitro propagation through mature seed explants.…”
Section: Introductionmentioning
confidence: 99%